Required peer-cooperative learning improves retention of STEM majors - Matthew Salomone; Thomas Kling (SpringerOpen, 2017)
Abstract Background Peer-cooperative learning has been shown in the literature to improve student success in gateway science and mathematics courses. Such studies typically demonstrate the impact of students' attending peer-led learning sessions on their learning or grades in an individual course. In this article, we examine the effects of introducing a required, comprehensive peer-cooperative learning system across five departments simultaneously at a master's public university, looking not only at students' success in supported classes, but also their retention within STEM fields two years hence. Combining institutional demographic data with students' course grades and retention rates, we compare outcomes between 456 students who took their major's introductory course in the two years prior to implementation of the program, and 552 students who did so after implementation. Results While these two student groups did not significantly differ in either their demographic profile or their SAT scores, the post-implementation group earned significantly higher grades in their introductory courses in each major, due largely to an erasure of the mediating effect of SAT scores on course grades. Further, this increase in introductory course grades was also associated with an increase in the two-year retention rate of students in STEM majors. Conclusions This finding is significant as it suggests that implementing comprehensive educational reform using required peer-led cooperative learning may have the proximate effect of mitigating differences in academic preparation (as measured by SAT scores) for students in introductory STEM courses. Furthermore, this increase in success leads to increased retention rates in STEM, expanding the pipeline of students retained in such fields.